Nursing Knowledge and Practice in Self-Care Compliance in Heart Failure Patients: A Systematic Review - Istianah, Istianah; Said, Faridah Binti Mohd; Nambiar, Nisha; Tohri, Tonika; Ramadhan, Muhammad Deri; Purwanti, Tentry Fuji; Juwita, Ninda Aina (Qualitative and Quantitative Research Center, 2024)
The disease that causes the number 1 death in the world is cardiovascular disease. Self-care involves maintaining possibilities by engaging in practices that enhance health. Monitoring symptoms and managing symptoms when they arise in patients with chronic diseases, including heart failure. This study aimed to explore knowledge and innovations that can be applied to Self-care with heart failure. The research method uses a systematic literature review. Research articles were obtained from three databases, namely Proquest, PubMed, and Google Scholar. Literature searches using keywords (in English), namely knowledge and practice, self-care, and heart failure, with Primary articles. The inclusion criteria used are articles from 2019-2023 in English. Primary articles, full text, and research subjects of patients with heart failure were reviewed from 1390 articles in eleven that met all criteria. Then, it was analyzed using simplified thematic analysis. The results show the themes that emerged from this literature review were the critical domain of self-care, the excellent impact of compliance, and monitoring innovations needed to reduce complications. Apart from that, telemonitoring is an outstanding innovation. The conclusion is that self-care for heart failure patients improves their quality of life and reduces complications. Adherence is critical, and innovations like telemonitoring applications enhance monitoring, proving effective in boosting patient welfare. This research contributes to providing readers with information about self-care strategies for heart failure patients to improve patient well-being.